ANALISIS PENGARUH PROPORSI DEWAN KOMISARIS INDEPENDEN DAN CHIEF FINANCIAL OFFICER WANITA TERHADAP REAL EARNINGS MANAGEMENT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2011 - Angelinda Fransisca; Hery Hery (Jurnal Akuntansi, 2015)
This study was conducted to provide empirical evidence of the influence of the proportion of independent board and women CFO towards real earnings management as measured by cash flow operations, production costs, and discretionary expenses. Testing is done by using multiple regression analysis, where the women CFO variables is dummy. The result showed that women CFO significant effect on real earnings management through cash flow operations and production costs, but not significant in real earnings management through discretionary costs. The variable proportion of independent board significant effect on real earnings management through discretionary expenses, but no significant effect on real earnings management through cash flow operations and production costs.